Training Needs Analysis (TNA) Regulatory Development Strategy to Increase the Effectiveness of Training Programs at PT BIB - Gemilaksono, Hari; Hermawan, Pri (CV. Syntax Corporation Indonesia, 2025)
The increasing production target of PT Borneo Indobara (PT BIB) to 54 million tons by 2026 necessitates strategic improvements in workforce competency through effective training programs. However, the current implementation of Training Needs Analysis (TNA) at PT BIB reveals significant gaps, including poor regulatory structure, minimal supervisor involvement, and inadequate post-training evaluation, resulting in misaligned training delivery. This research aims to analyze the TNA process, evaluate training effectiveness, identify influencing factors, and develop a structured regulatory strategy using the RACI Matrix approach. Employing a mixed-methods design, the study integrates qualitative methods (interviews and observations) with quantitative analysis (descriptive statistics, mean ranking, and Pearson correlation) involving 150 respondents. The results demonstrate that the absence of formal TNA regulations and limited stakeholder engagement undermine the alignment between training programs and operational realities. The implementation of the RACI Matrix significantly clarifies roles and responsibilities across departments, particularly enhancing the involvement of supervisors, and is associated with a marked improvement in training effectiveness (p < 0.001). The study concludes that adopting RACI-based TNA regulations, coupled with performance-focused evaluation systems and periodic monitoring, can significantly enhance employee competence and contribute to the achievement of corporate goals. This research offers a novel, practical framework for improving training governance and invites further longitudinal exploration on the sustainability and broader applicability of the proposed model.